Application of Bokashi Botom Ash for Increasing Upland Rice Yield and Decreasing Grain Pb Content in Vitric Hapludans - Nunung Sondari; Ervina Siti Nurkhalidah (JOURNAL OF TROPICAL SOILS, 2012)
Greenhouse experiment was conducted at Agricultural Faculty of Winaya Mukti University Tanjungsari SumedangRegency, from May to October 2009. The objective of this experiment was to study the effect of bokashi bottom ashon the growth, yield, and Pb content of upland rice. The experiment used a Randomized completely Block Design(RBD) which consisted of five treatments and five replications. The treatments were level of bokashi bottom ash i.e.0, 5, 10, 15, and 20 Mg ha-1. The results showed that the application of bokashi bottom ash increased the growth andyield of upland rice of Situbagendit variety except plant height at age of 21 days after seedling (DAS). Application15 Mg ha -1 of bokashi bottom ash gave the best effect to the plant height, number of leaves, number of tillers andshoot/root ratio, while applications of 10, 15 and 20 Mg ha -1 increased number of productive tillers, amount of filledgrains, and weight of grains. Bokashi bottom ash did not affect the heavy metal content of upland rice grain ofSitubagendit variety.[How to Cite: Sondari N and ES Nurkhalidah. 2012. Application of Bokashi Botom Ash for Increasing Upland Rice Yield and Decreasing Grain Pb Content in Vitric Hapludans. J Trop Soils 17 (2) : 157-163. Doi: 10.5400/jts.2012.17.2.157] [Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.2.157]